ANALISIS PENGARUH LINGKUNGAN KERJA TERHADAP DISIPLIN KERJA KARYAWAN PADA PT. RPJ - Niken Herawati; Asrah Tandirerung Ranteallo (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2019)
This study aims to determine the effect of the work environment and employee discipline on PT RPJ. The type of research used in this study is explanatory research or explanatory research with a quantitative approach, by testing the correlation coefficient, determination and similar simple regression. Data processing is assisted by using the SPSS version 22 statistical program, and the data collection techniques used in this study are using the method of observation, interviews, questionnaires and documentation studies, with a total sample of 32 respondents, all of whom are employees of PT RPJ. From this study the results show that the work environment has a positive and significant influence on employee work discipline in PT RPJ, amounting to 76.8% and the remaining 23.2% is influenced by other variables not analyzed in this study.